PENGARUH PROMOSI DAN PELAYANAN TERHADAP PENCAPAIAN TARGET KONSUMEN PADA PERUMAHAN BUMI CIRUAS PERMAI 2 - Fatari, Fatari (UP2M SEKOLAH TINGGI ILMU EKONOMI GALILEO, 2018)
The purpose of this study was to determine the effect of promotion on the achievement of consumer targets in Bumi Ciruas Permai Housing 2, to determine the effect of service on achieving consumer targets in Bumi Ciruas Permai Housing 2, as well as to determine the effect of promotion and service on achieving consumer targets in the Ciruas Earth Housing Permai 2.Â The method in this research is descriptive quantitative research which aims to find out how the level of service quality delivered by Bumi Ciruas Permai housing business in Ciruas to its customers. Descriptive research is research that is used to determine the attribute values independently, either one or more, without making comparisons or linking them with other elements. SPSS version 21 calculation results obtained t-count value of 0.929 and t-table of 1.987, indicating that the value of t count <t table (2.285 <1.987). The results of the calculation of SPPS version 21 obtained the t-count value of 0.929 and the t-table value of 1.987, indicating that the value of t-count <t-table (0.929> 1.987). Based on the results of the SPSS version 21 calculation obtained a correlation coefficient of 0.535 it can be concluded that between the promotion variable (X1) and service (X2) to the target consumer ignition (Y) has a strong enough relationship. 0,535 is at the interval coefficient 0,300 - 0,499 (medium). The calculation results obtained by the value of fcount> ftabel (17.066> 3.10).Â There is no promotion effect (X1) on the target consumer ignition (Y) on Bumi Ciruas Permai Housing 2. There is an influence between service (X2) on the target consumer ignition (Y) on Bumi Ciruas Permai Housing 2. There is a simultaneous influence between promotions (X1 ) and service (X2) to the target consumers ignition (Y) at Bumi Ciruas Permai Housing 2.Â